Implementation of IPOS 4.0 for Entrepreneurship Learning for Environmental Sanitation Students - Frida Hendrarinata; Triana Septianti Purwanto; Hery Koesmantoro (Humanistic Network for Science and Technology (HNST), 2026)
The rapid development of digital technology has encouraged educational institutions and student cooperatives to adopt integrated financial management systems to improve transparency, accuracy, and operational efficiency. However, many campus based cooperatives still rely on manual bookkeeping, which is prone to delays, inconsistencies, and limited financial analysis capacity. This study aims to analyze the effectiveness of implementing the IPOSPRO digital bookkeeping application at KOPMA Magetan Campus Environmental Sanitation, focusing on improvements in sales recording, inventory management, and profit–loss reporting. A participatory action research (PAR) design was employed, consisting of planning, acting, observing, and reflecting stages. Data were collected through direct observation, documentation of manual and digital financial reports, and evaluation of student performance during system operation. The results show that the implementation of IPOSPRO significantly enhanced the accuracy and speed of transaction recording, enabling real time updates and reducing human error compared to manual methods. Inventory management became more transparent and synchronized, as stock levels were automatically updated with each transaction, minimizing discrepancies between physical and recorded stock. Profit and loss reporting also improved, with the system generating automated and more comprehensive financial summaries based on integrated sales, purchase, and stock data. Additionally, the use of IPOSPRO strengthened students’ digital literacy and practical entrepreneurial skills, although several challenges remained, including difficulties in stock synchronization, inconsistent data input, and limited understanding of digital financial reports. In conclusion, the IPOSPRO application improves transaction accuracy, stock transparency, and financial reporting while enhancing students’ digital literacy, although continuous training and technical support are still required. Keywords: digital bookkeeping, IPOSPRO, inventory management, financial reporting, student cooperative, digital literacy.